EVALUASI BUKU KRITIK SENI UNTUK MAHASISWA PADA PROGRAM STUDI PENDIDIKAN SENI RUPA FAKULTAS SENI DAN DESAIN UNIVERSITAS NEGERI MAKASSAR - Pangeran Paita Yunus; Siti Asmaulul Izmi; Faidhul Inayah (Universitas Negeri Makassar, 2023)
Forming the character of a student who has a critical nature towards various issues of art and how to understand, respond and provide comments on the works of art they encounter, can be started through Art Criticism courses taught at universities. Basically, the knowledge about art criticism obtained by students can be used as a bridge between artists as creators of works of art and critics as reviewers, so that a dialogue occurs between works of art created by artists and observers (appreciators). The Art Criticism course not only provides a theoretical basis for the concept of Art Criticism but shapes a student's attitudes, behavior and mindset. This is a capital investment to prepare students to start activities in their lives after studying at university. Through the integration of the experience, skills and knowledge they have acquired, students can develop themselves to become art observers or art critics. This research aims to evaluate the suitability of the Art Criticism textbook with the criteria for a good textbook prepared by the Ministry of Education and Culture. The product evaluated in this research is teaching material in the form of an Art Criticism textbook. The Art Criticism course is one of the mandatory courses for students of the Fine Arts Education study program, FSD Fine Arts Education study program, Makassar State University. This research evaluates the teaching materials of the Art Criticism textbook and then measures the appropriateness of the content, appropriateness of presentation, language and source material.